2012
DOI: 10.1590/s0103-64402012000600002
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride modulates preosteoblasts viability and matrix metalloproteinases-2 and -9 activities

Abstract: This study evaluated the influence of fluoride on cell viability and activity of matrix metalloproteinases (MMP) -2 and -9 secreted by preosteoblasts. Preosteoblasts (MC3T3-E1 murine cell line) were cultured in MEM medium supplement with 10% Fetal Bovine Serum (FBS) and nucleosides/ribonucleosides without ascorbic acid. Adherent cells were treated with different concentrations of F (as sodium fluoride-NaF) in medium (5 x 10 -6 M, 10 -5 M, 10 -4 M and 10 -3 M) for 24, 48, 72 and 96 h at 37 o C, 5% CO 2 . Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
1
8
0
3
Order By: Relevance
“…Several studies have shown that millimolar levels of F can induce apoptosis in many cell types, including hepatic cells, epithelial lung cells, human leukemia HL-60 cells, and ameloblast-lineage cells. [27][28][29][30] We have also shown that F increases apoptosis in hippocampal and osteoblast-like cells. 10 However, other mechanisms can be involved in F-mediated cell death, such as endoplasmic reticulum stress.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Several studies have shown that millimolar levels of F can induce apoptosis in many cell types, including hepatic cells, epithelial lung cells, human leukemia HL-60 cells, and ameloblast-lineage cells. [27][28][29][30] We have also shown that F increases apoptosis in hippocampal and osteoblast-like cells. 10 However, other mechanisms can be involved in F-mediated cell death, such as endoplasmic reticulum stress.…”
mentioning
confidence: 71%
“…It has also been found that high concentrations of F resulted in the upregulation of MMP-2 and MMP-9 in pro-osteoblast cells. 30 However, it has been also suggested that an oral hygiene regimen based on amine/ stannous fluoride-containing toothpaste is effective in reducing plaque-associated gingivitis and gingival inflammation. 40 Of note, AgNPs cause inflammation in other cell types, such as liver cells both in vivo and in vitro.…”
mentioning
confidence: 99%
“…Nesse trabalho também avaliamos a expressao gênica da MMP-2 em diversos períodos experimentais frente a utilização do extrato de aroeira. As MMPs contribuem tanto para a remodulação tecidual normal quanto patológica (SLOMPO et al, 2012). Os papéis fisiológicos das MMPs incluem a migração celular, a remodelação do tecido durante organogênese e crescimento, cicatrização de feridas, 6 Discussão 98 a angiogênese e formação do esmalte (HANNAS et al, 2007;TOCCHI & PARKS, 2013).…”
Section: Discussionunclassified
“…As MMPs pertencem à família de proteinases zinco dependentes neutras (SOUZA & LINE, 2002). Entre os representantes das MMPs encontram-se as chamadas gelatinases A ou MMP-2 (72 kDa) tipo colagenase IV e gelatinase B ou MMP-9 (92 kDa) que degrada especialmente o colágeno tipo IV e regula o remodelamento das membranas basais (MAKELA et al, 1994;SLOMPO et al, 2012).…”
Section:  Osteoclastosunclassified
See 1 more Smart Citation